Endotoxin Contamination in Nanomaterials Leads to the Misinterpretation of Immunosafety Results - Li, Yang; Fujita, Mayumi; Boraschi, Diana (Frontiers in Immunology, 2017)
Given the presence of engineered nanomaterials in consumers' products and their application in nanomedicine, nanosafety assessment is becoming increasingly important. In particular, immunosafety aspects are being actively investigated. In nanomaterial immunosafety testing strategies, it is important to consider that nanomaterials and nanoparticles are very easy to become contaminated with endotoxin, which is a widespread contaminant coming from the Gram-negative bacterial cell membrane. Because of the potent inflammatory activity of endotoxin, contaminated nanomaterials can show inflammatory/toxic effects due to endotoxin, which may mask or misidentify the real biological effects (or lack thereof) of nanomaterials. Therefore, before running immunosafety assays, either in vitro or in vivo, the presence of endotoxin in nanomaterials must be evaluated. This calls for using appropriate assays with proper controls, because many nanomaterials interfere at various levels with the commercially available endotoxin detection methods. This also underlines the need to develop robust and bespoke strategies for endotoxin evaluation in nanomaterials.